Lockdown influence on diet and physical activity of seniors; has it weight consequences - Kaňuková, Lívia; Rimárová, Kvetoslava; Dorko, Erik; Makovický, Pavol; Kopecký, Miroslav; Kubalcová, Paulína (Central European journal of public health, 2024)
OBJECTIVES: Many studies draw attention to the negative consequences of the pandemic or lockdown on the well-being and lifestyle of different sections of the population. This study considers whether changes occurred in dietary regime and level of physical activity during three periods - before the pandemic, during the lockdown, and during the present in older Slovak adults. We also investigate whether individual weights changed during the pandemic. METHODS: The study has a cross-sectional design. We collected 436 questionnaires from older adults (60+) living in Slovakia; 277 come from the first phase of online data collection (04/2022-06/2022) in university students of the third age, and 159 from the second phase of offline collection (07/2022-11/2022) in social service facilities. We monitored if there were any changes within the observed periods in the variables of diet regime, physical activity, and BMI. The database has been processed in IBM SPSS Statistics. RESULTS: During the lockdown, the frequency of physical activity decreased (p < 0.001), the quality of movement worsened (p < 0.001), and the time respondents devoted to physical activity during the week decreased (p < 0.001). At present, the variables have increased. Within the dietary regimen, statistically significant changes occurred in appetite and non-alcoholic beverage intake (p = 0.002). However, there were no significant changes in the number of daily meals (p = 0.190), or the amount of alcohol consumed (p = 0.066). The BMI of older men and women did not change after the pandemic (p = 0.519), and it did not differ between men and women either before the pandemic (p = 0.281) or after it (p = 0.449). Also there is no difference between UTA students and social facility living seniors before the pandemic (0.933) and now (0.317). The results showed that even though physical activity significantly decreased during the lockdown, the older adults in our study did not eat more during the lockdown, nor did they gain weight. However, this probably had negative consequences for the quality of their movement. CONCLUSION: It is essential to simultaneously create compensatory measures while implementing future anti-epidemic (or other) measures. They would help maintain the desired amount of physical activity or other healthy habits on an optimal level.
Keywords: karanténa; Exercise; senioři nad 80 let; průzkumy a dotazníky; Humans; lidé; Body Weight; Quarantine; lidé středního věku; cvičení; pandemie; Middle Aged; Aged, 80 and over; Surveys and Questionnaires; Female; Male; Slovakia; Pandemics; Slovenská republika; Body Mass Index; COVID-19; mužské pohlaví; Aged; dieta; index tělesné hmotnosti; ženské pohlaví; Cross-Sectional Studies; průřezové studie; tělesná hmotnost; Diet; SARS-CoV-2; senioři